Management of Oral Mucositis in Children With Malignant Solid Tumors - Attinà, Giorgio; Romano, Alberto; Maurizi, Palma; D’Amuri, Sara; Mastrangelo, Stefano; Capozza, Michele Antonio; Triarico, Silvia; Ruggiero, Antonio (Frontiers in Oncology, 2021)
Introduction: In recent years, the use of intensive regimens for the treatment of pediatric cancer has led to a marked improvement in patient survival. However, these treatments are associated with an increase in toxic effects. Among these side effects, mucositis (inflammation of the oral cavity) significantly affect the success of treatment. The aim of this study was to assess the prevalence of mucositis in a pediatric population, identify the risk factors that influence its occurrence, and verify the usefulness of pain rating scales. Methods: We registered episodes of mucositis which occurred in a sample of 84 consecutive children with solid tumors between 1 January, 2012 and 30 April, 2018. The World Health Organization (WHO) oral mucositis grading scale and the modified Wong–Baker FACES Pain Rating Scale (WBS) were used to assess the severity of each episode. Moreover, data on the treatments used and blood count results were collected. Results: The prevalence of mucositis in our population was 50%, without statistically significant difference according to sex and a higher prevalence observed in patients aged >10 years. The presence of neutropenia, higher number of cycles of chemotherapy, and co-existence of lymphomas and sarcomas were identified as factors favoring the occurrence of mucositis. The WBS showed results superimposed on the WHO oral mucositis grading scale in choosing the intensity and duration of mucositis treatment. Conclusion: Oral mucositis is a common complication of chemotherapy against childhood malignancies. The WHO oral mucositis scale is a valuable tool for assessing its severity in pediatric patients. Furthermore, WBS can be used as an assessment tool to establish the therapy to be adopted for patients in whom direct evaluation of the oral cavity is not possible.